ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM SETELAH PEMBERLAKUAN ROAD MAP MENUJU BUMN BERSIH - Al Amin, Nanda Adib; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to provide empirical evidence of differences of financial performance of the company, before and after the implementation of Circular Letter of state ministries of State Owned Enterprises No. 05/MBU/2013 about the Roadmap towards clean State Owned Enterprises. The financial performance is measured by using profitability ratio, liquidity ratio, and leverage ratio. Meanwhile, Good Corporate Governance (GCG) is carried out by using the Circular Letter of state ministries of State Owned Enterprises No. 05/MBU/2013. The results showed the companys financial performance before and after the enactment of Circular of the Ministry of State-Owned Enterprises No. 05 / M BU / 2013 About Road Map Towards a Clean State Owned Enterprises shown to have a significant difference. Meanwhile, the results of hypothesis testing Return On Investment and Net Profit Margin resulted in a significant difference, while the Current Ratio, Quick Ratio, Debt Ratio, and Debt To Equity ratio shows the results no significant difference before and after the application of Circular of the Ministry of State-Owned Enterprises No. 05 / MBU / 2013 About Road Map Towards clean State Owned Enterprises. Significant differences Return On Investment and Net Profit Margin before and after the application of the Circular of the State Ministry of State-Owned Enterprises No. 05 / MBU / 2013 due to changes in the companys working system to meet the pillars upholding GoodCorporate Governance contained in the Circular. The absence of a significant difference to the Current Ratio, Quick Ratio, Debt ratio and Debt To Equity Ratio is due to the company in establishing the pillars of good corporate governance in the form of the companys work system change impact rising value of the company (Corporate Asset) due to the emergence of corporate debtKeywords: Good Corporate Governance, Circular Letter of Ministry State of BUMN No. 05/MBU/2013,Financial Performance.